Adoption of agricultural technology and its recent impact on agricultural development in Murshidabad district of West Bengal, India - Mumtaj Ahmad,; Asefa Khatun,; Md. Ali Jinnah, (National Geographical Journal of India, 2023)
Agriculture and allied sector play an important role in the Indian economy. It employs nearly 54.6 per cent of the population and contributes 17.4 per cent of the gross domestic product in India (Census, 2011). Among the various factors, technology is crucial for agricultural development. West Bengal is one of the leading agrarian states in India. According to agricultural census data of West Bengal, the total food grain produced in 2021 is 20.110 tons million. The present study attempts to examine the level of agricultural development in terms of technology in the Murshidabad district of West Bengal. Murshidabad contributes the highest in food production. It also enjoys a favourable climate, suitable soil, and availability of labour. About 76 per cent of the total land area is under cultivation. Eleven variables are considered related to agricultural development and machinery. Data is collected from the Agriculture Department, Murshidabad district, 2015-16, Bureau of Applied Economics and Statistics, Government of West Bengal, 2015-16, District Statistical Handbook, Murshidabad district, 2013-14, and other secondary sources. To draw a relation Z-score, Composite Z-score, and Carl Pearson’s correlation coefficient are calculated. Arc GIS is used for mapping. Based on agricultural development and the use of technology blocks are categorized into high, medium, and low levels. Providing high-yield varieties of seeds, proper irrigation facilities, organic and chemical fertilizers, and other institutional facilities can help the blocks with low and medium levels of agricultural development and minimize food insecurity and unemployment in the district.